Wajah Islam Liberal di Indonesia: Sebuah Penjajagan Awal - Zuly Qadir (Al-Jami'ah: Journal of Islamic Studies, 2002)
This article tries to describe contemporary Islamic thought in Indonesia, which is influenced by modern and critical social sciences. The Islamic Liberalism is considered by some people as a new school (madzhab) in the Indonesian Islamic thought. What is the relevance of the Islamic Liberalism while Indonesia in economic crisis? Who are the figures of the Islamic Liberalism in Indonesia? The Islamic Liberalism mostly concerned with how Islam deals with modernity such as democracy, pluralism, the state, gender, etc. The methodology of the Islamic Liberalism is to perceive new interpretation toward Islamic doctrine of Al-Qur'an and Hadith, social history and social context of Muslim society by employing the science of language, historical critics and social sciences. Nurcholish Madjid, Qohan Effendy, Abdurrahman Wahid and Ahmad Wahib are among those who set the embryo of the Islamic Liberalism in Indonesia. After them, some young intellectuals from NU, Muhammadiyah and other NGOs have been developing and becoming the avant-gardes of the Islamic Liberalism. They have a distinct thought that is not sectarian, ideological and parochial. How is the future of this new genre of Islamic thought in Indonesia? To understand them, we should have a look at their activities either theoretically (discourses) or practically.